Differences in heart rate parameters of competitive performances in boxing and kickboxing - Žaja, M.; Sertic, H.; Segedi, I. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Physiological activity load is one of the main criteria for e cient training programming. The problem of the study is reflected in the fact that, although boxing and kickboxing belong to the group of polystructural sports in which the result is achieved by similar technical-tactical means, there are still certain di erences in the physiological load of the competitive performance itself. The aim of this study is to determine di erences in heart rate indicators (average and maximum heart rate during the three rounds) between competitive performances in two striking combat sports: boxing and kickboxing. The sample of subjects in this study consists of 20 athletes who practice the striking combat sports boxing and kickboxing. For the purposes of the study, the subjects fought each other according to boxing rules and K-1 discipline rules in kickboxing in a simulated competitive environment. The results have shown that the heart rate in both sports continuously increases during all three rounds, and the oscillations in the heart rate are more pronounced in kickboxing than in boxing, but only statistically signi cant di erence was found in variable mean heart rate during the third round of boxing and kickboxing bout - HR AVG 3 B/KB (p 0,041). The results indicate that in a boxing ght there is a continuous increase in heart rate, while in a kickboxing ght the heart rate in the third round decreases signi cantly. From these results, it can be concluded that kickboxers drop in the rhythm of the ght in the third round. This may suggest that kickboxers fail to maintain a high rhythm of the fight in the third round probably due to the di erent structural characteristics of kickboxing sport and the bout itself.